2019
DOI: 10.21037/jtd.2019.04.69
|View full text |Cite|
|
Sign up to set email alerts
|

Simple pre-procedure risk stratification tool for contrast-induced nephropathy

Abstract: Background: A few simple and pre-procedural risk models have been developed for predicting contrastinduced nephropathy (CIN), which allow for early administration of preventative strategies before coronary angiography (CAG). The study aims to develop and validate simple pre-procedure tools for predicting risk of CIN following CAG. Methods: We retrospectively analyzed the data from 3,469 consecutive patients undergoing CAG, who were randomly assigned to a development dataset (n=2,313) and a validation dataset (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…However, the incidence data reported in Germany, Brazil and Iran were significantly higher, which may be associated with the number of studies and patient characteristics. The patients included in the studies from Germany were elderly, and this was a risk factor for CA-AKI [ 33 , 34 ]. The increased incidence in Brazil and Iran may be related to the small number of patients included.…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence data reported in Germany, Brazil and Iran were significantly higher, which may be associated with the number of studies and patient characteristics. The patients included in the studies from Germany were elderly, and this was a risk factor for CA-AKI [ 33 , 34 ]. The increased incidence in Brazil and Iran may be related to the small number of patients included.…”
Section: Discussionmentioning
confidence: 99%
“…Since Mehran first developed a risk scoring system, which involves eight clinical and procedural variables, to predict CIN after PCI, several simpler risk assessment models have been proposed [ 21 , 86 , 87 , 88 , 89 ]. The ACEF (age, creatinine, and ejection fraction) score was originally developed in 2009 to assess the mortality risk in patients undergoing elective cardiac operations, but that simple risk scoring system has subsequently been validated in other clinical conditions, including CIN after CAG or PCI.…”
Section: Managementmentioning
confidence: 99%
“…AMI, hypotension and HS-CRP are the research hotspots of CA-AKI and prognosis. The association between AMI and CA-AKI has been confirmed in previous studies [26,27], and Zafrir et al also found that patients with AMI can have significantly increased long-term mortality [28]. Hypotension, as a strong predictor of CA-AKI, is also a good predictor of death.…”
Section: Discussionmentioning
confidence: 59%